MENINGKATKAN KETERAMPILAN KOLABORASI DENGAN MODEL PEMBELAJARAN LITERATURE CIRCLE PADA PESERTA DIDIK KELAS V SD (PTK PADA PEMBELAJARAN IPS KERAGAMAN BUDAYA) - Nadia Syavira; Julius Sagita; Indah Trismawanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Collaboration is one of the skills that students must have in the 21st century. However, in reality students' collaborative attitudes are still less visible because the learning methods and models used are rarely in the form of groups. The purpose of this research is to improve students' collaboration skills using the Literature Circle learning model in learning cultural diversity in fifth grade elementary school. This research was a class action research conducted for 2 cycles. The subjects of this study were 27 people from class 5 A. The data collection from this study was based on observations made collaboratively between researchers and observers based on the observation sheets that had been prepared. . The collected data were analyzed by descriptive statistical analysis. The results showed that the average collaborative attitude in Cycle I was 44%, so learning continued in Cycle II. In Cycle II, the average result of students' collaborative attitudes was 76%. Based on the results of the study it can be concluded that the Literature Circle learning model is effective in improving students' collaboration skills regarding learning cultural diversity.